Lessons of the month: Pyroglutamic acidosis: long-term paracetamol and a high anion gap. Issue 5 (2020) - Trevor-Jones, Emma; Hughes, Lewis T; Robson, Rebecca; Bromley, Alan; Stewart, Gordon W
No abstract available